Growth of preference for solitude in urban and rural Chinese adolescents - Chen, Xi; Sun, Xinxin; Wu, Xuan; Liu, Junsheng; Li, Dan; Chen, Xinyin (Frontiers in Psychiatry, 2023)
Introduction As individuals enter adolescence, their preference for solitude (PFS) increases with age, which may be a result of balancing the need for social affiliation and the need for autonomy and independence. These needs are shaped by the social-cultural contexts, and thus the growth rate of PFS may differ across social-cultural contexts.This study examined to what extent the developmental trajectory of PFS differed between urban and rural Chinese adolescents. Methods Adolescents in urban (n = 326,168 boys, Mage =12.00 years, SD = 0.61) and rural (n = 449, 198 boys, Mage =11.82 years, SD = 0.58) regions in China reported their PFS and shyness each year from Grade 6 to Grade 8. Longitudinal measurement invariance of PFS was established between the urban and rural samples. Location and gender differences in the intercept and the slope of PFS were examined using a latent growth model, while controlling for shyness at each time point. Results The analyses revealed that adolescents in both urban and rural regions showed an increasing trajectory of PFS. Although urban and rural adolescents did not differ in the initial level of PFS at Grade 6, urban adolescents’ PFS increased faster than that of the rural adolescents. The urban-rural difference in the slope of PFS remained significant after controlling for the associations between the intercept and the slope of PFS and shyness at each time point. In addition, in the rural region, boys showed a faster increase of PFS than girls, yet gender differences in the initial level of PFS and the developmental trajectory in the urban region were nonsignificant. Discussion The findings reveal a normative increasing trend of PFS during early adolescence and faster increase for urban than rural adolescents. To promote adolescents’ psychological well-being, parents, teachers and practitioners need to help adolescents establish a good balance between social interaction and solitude. When deciding what is a good balance, it is important to consider the social-cultural context.